2022
DOI: 10.1186/s13054-022-04148-0
|View full text |Cite|
|
Sign up to set email alerts
|

Obesity and critical care nutrition: current practice gaps and directions for future research

Abstract: Background This review has been developed following a panel discussion with an international group of experts in the care of patients with obesity in the critical care setting and focuses on current best practices in malnutrition screening and assessment, estimation of energy needs for patients with obesity, the risks and management of sarcopenic obesity, the value of tailored nutrition recommendations, and the emerging role of immunonutrition. Patients admitted to the intensive care unit (ICU)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 95 publications
0
9
0
1
Order By: Relevance
“…In addition, patients who have obesity are more likely to be admitted to the Intensive Care Unit post-trauma [ 17 ]. In the critical care setting, the provision of adequate nutrition support to patients who have severe obesity is challenging [ 42 ], and patients who have obesity appear to have lower mortality but an increased risk of complications in several organ systems [ 18 ]. Obesity is also an independent risk factor for hospital readmission following surgery, such as total joint arthroplasty [ 43 ], cardiac surgery [ 41 ], and exacerbation of chronic health conditions [ 38 , 44 ], including mental health conditions [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, patients who have obesity are more likely to be admitted to the Intensive Care Unit post-trauma [ 17 ]. In the critical care setting, the provision of adequate nutrition support to patients who have severe obesity is challenging [ 42 ], and patients who have obesity appear to have lower mortality but an increased risk of complications in several organ systems [ 18 ]. Obesity is also an independent risk factor for hospital readmission following surgery, such as total joint arthroplasty [ 43 ], cardiac surgery [ 41 ], and exacerbation of chronic health conditions [ 38 , 44 ], including mental health conditions [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Due to the di culty of swallowing and decreased appetite caused by tumor compression, patients often face the problem of insu cient nutritional intake in the early stage. In addition to the decrease in oral intake, tumor-related cachexia, decreased digestive ability, decreased gastrointestinal function, increased catabolism, and side effects of radiotherapy and chemotherapy all exacerbate the decline in the patient's nutritional status 12,13 .…”
Section: Discussionmentioning
confidence: 99%
“…Other authors advocate higher doses as 2–2.5 g/kg/day of ideal body weight, but there have been no studies assessing the benefits of such high doses in this specific population [22]. A recent retrospective analysis of mechanically ventilated adult critically ill patients, not considering overweight and obesity, showed that those individuals with low skeletal muscle area and density who received early increased intake of proteins had lower mortality.…”
Section: Nutritional Management During Critical Illnessmentioning
confidence: 99%